Relatório de estágio supervisionado obrigatório - Matos, Genoveva Pinheiro (Brasil, 2025)
The internship was carried out by Amazonas Leite, with extension at the Agro Nova farm, with the objective of monitoring and practical application of academic knowledge, through the rural extension carried out by the Amazonas Leite Extension program at the Agro Nova private property, in order to collaborate with the development of production, using management methods adopted in the breeding system. Having as activities developed the milking management, displacement of sows to the milking parlor, bathing the animals, cleaning of the udder and teat, hygiene of the milking, manual milking, milk control, lactation of the calves, feeding of the sows, availability of concentrate, availability of forage, cleaning of the milking room, cleaning of the drinkers, verification of the pasture and weeding, maintenance of the feeding pen, silage storage. When working in the extension area, it is of fundamental importance that you have this experience, to carry out the activities and solve problems arising from the day-to-day life of the professional in the area of Animal Science. The use of rational animal management was already being carried out and because they are dairy cows, other methods of hygiene in the milking parlor, handler and feeding were adopted to better conduct the activities carried out.